Real-time PCR: Concept and Application in Livestock - Dige, Mahesh S.; Kokate, L. S.; Inamdar, B.; Kumar Das, Ananta (International Journal of Bio-resource and Stress Management, 2023)
Real-time PCR, also called quantitative PCR or RT-qPCR, is a technique which provide a simple and elegant method for determining the amount of a target sequence or gene that is present in a sample. It is a gold standard method for accurate and sensitive quantification of nucleic acid sequences. It completely revolutionizes the way one approaches PCR-based quantitation of DNA and RNA. Traditional PCR had the drawbacks like poor precision, low sensitivity, low resolution, Post-PCR processing etc., which are being eliminated by RT-qPCR. RT-qPCR requires dedicated instruments that are able to quantify amplification products in real-time during each cycle. The simplest detection technique for newly synthesized PCR products uses SYBR Green I fluorescence dye that binds specifically to the minor groove ds-DNA. The quantification method of choice depends on the target sequence, the expected range of the nucleic acid amount present in the tissue, the degree of accuracy required and whether quantification needs to be relative or absolute. Furthermore, a normalisation of the target gene with an endogenous standard is recommended. However, the reproducibility of RT-qPCR result varies greatly between tissues, isolation methodology and the reagents used. Therefore, MIQE provides a checklist for preparing a report of the RT-qPCR study. It allows reviewers to evaluate the work and other investigators to reproduce it.